Exfoliated Human Deciduous Tooth Stem Cells Incorporating Carbonate Apatite Scaffold Enhance BMP-2, BMP-7 and Attenuate MMP-8 Expression During Initial Alveolar Bone Remodeling in Wistar Rats (Rattus norvegicus) - Prahasanti C; Nugraha AP; Saskianti T; Suardita K; Riawan W; Ernawati DS (Dove Medical Press, 2020)
Chiquita Prahasanti,1 Alexander Patera Nugraha,2,3 Tania Saskianti,4 Ketut Suardita,5 Wibi Riawan,6 Diah Savitri Ernawati7 1Department of Periodontology, Faculty of Dental Medicine, Airlangga University, Surabaya, Indonesia; 2Department of Orthodontics, Faculty of Dental Medicine, Airlangga University, Surabaya, Indonesia; 3Medical Science, Faculty of Medicine, Airlangga University, Surabaya, Indonesia; 4Department of Pediatric Dentistry, Faculty of Dental Medicine, Airlangga University, Surabaya, Indonesia; 5Department of Conservative Dentistry, Faculty of Dental Medicine, Airlangga University, Surabaya, Indonesia; 6Department of Biomolecular Biochemistry, Faculty of Medicine, Brawijaya University, Malang, Indonesia; 7Department of Oral Medicine, Faculty of Dental Medicine, Airlangga University, Surabaya, IndonesiaCorrespondence: Chiquita PrahasantiDepartment of Periodontology, Faculty of Dental Medicine, Universitas Airlangga, Jl. Prof. Dr. Moestopo 47, Surabaya, IndonesiaTel/Fax +62 31 5030255Email chiquita-p-s@fkg.unair.ac.idBackground: Post-tooth extraction socket preservation is necessary due to alveolar bone resorptive patterns through regenerative dentistry approaches that involve the use of stem cells, scaffold and growth factor. Stem cells derived from human exfoliated deciduous teeth (SHED) are known to potentially possess the osteogenic ability. Meanwhile, carbonate apatite scaffold (CAS) can act as a biocompatible scaffold capable of supporting mesenchymal stem cells (MSCs) to proliferate and differentiate optimally. The aim of this study is to investigate the expression of bone morphogenic protein-2 and 7 (BMP2, BMP7) and Matrix Metalloproteinase-8 (MMP-8) after the transplantation of SHED-incorporated CAS during in vivo bone remodeling.Material and Methods: A total of  14 healthy, male, Wistar rats, whose mandible anterior teeth were extracted by means of sterile needle holder clamps, constituted the subjects of this study of alveolar bone defects. Two research groups were created: a control group (CAS) as group I and an experimental group (CAS + SHED) as group II. SHED with a density of 106 cells were incorporated into CAS before being transplanted into the experimental group. After 7 days, all the animals were sacrificed and their mandible anterior region extracted. The BMP2, BMP7 and MMP-8 expression were subsequently analyzed by means of immunostaining. An unpaired t-test was conducted to analyze the treatment and control group (p< 0.01) data.Results: The expression of BMP-2 and BMP-7 was higher in group II compared to group I. Meanwhile, the level of MMP-8 was lower in group II than group I. There was greater significant increased expression of BMP-2 and BMP-7 expression in Group II compared to Group I. There was significant decreased expression of MMP-8 between group II than group I (p< 0.01).Conclusion: SHED-incorporated CAS can enhance BMP-2 and BMP-7 expression while attenuating MMP-8 expression during in vivo alveolar bone remodeling.Keywords: alveolar bone defect, bone regeneration, carbonate apatite scaffold, osteogenic ability, stem cell from human exfoliated deciduous teeth